Porous magnesium structure for storing hydrogen, method for manufacturing same, and method for
By using a porous magnesium structure as a hydrogen storage material, the problems of low energy loss and density in the existing hydrogen storage methods are solved, and the effect of rapid absorption and desorption of hydrogen at low temperatures is achieved. The preparation method of this structure is environmentally friendly and simple, which promotes the development of the hydrogen economy.
Patent Information
- Application Number
- CN202380050880.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-09-12
- Filing Date
- 2023-10-04
- Publication Date
- 2025-04-11
AI Technical Summary
Existing hydrogen storage methods suffer substantial energy losses during storage, low volume storage density, and the temperature required for hydrogen absorption/desorption using expensive carbon fibers, metal hydrides or composite hydrides is too high or the absorption/desorption rate is too slow.
A porous magnesium structure is used as a hydrogen storage material. The structure includes a magnesium framework and pores, with a three-dimensional porous structure. The average thickness of the magnesium framework is between 0 nm and 50 nm. The oxide film and transition metal can exist on the surface of the magnesium framework. By preparing this structure in a non-corrosive solution, rapid absorption and desorption of hydrogen are achieved.
Rapid absorption and desorption of hydrogen at low temperatures has high energy density and high safety, and the preparation method is environmentally friendly and simple, which is suitable for promoting the development of the hydrogen economy.
Smart Images

Figure CN119816609A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a porous magnesium structure for storing hydrogen, a preparation method thereof and a method for storing hydrogen.
[0002] Related technologies
[0003] The current commercial hydrogen storage method is a physical storage method that compresses hydrogen under high pressure or stores hydrogen at ultra-low temperatures. However, physical hydrogen storage suffers from large energy losses during storage, has low volumetric storage density, and uses expensive carbon fibers.
[0004] To address these issues, metal hydrides or composite hydrides have been widely studied as solid hydrogen storage materials with high energy density and high safety, but their disadvantages are that the temperature required for hydrogen absorption / desorption is too high or the absorption / desorption rate is too slow.
[0005] Details of the invention
[0006] Technical issues
[0007] One example provides a porous magnesium structure for storing hydrogen that allows rapid absorption and desorption of hydrogen at low temperatures.
[0008] Another example provides an environmentally friendly and simple method for fabricating porous magnesium structures for hydrogen storage.
[0009] Another example provides a method of storing hydrogen using a porous magnesium structure.
[0010] Technical Solution
[0011] According to an example, a porous magnesium structure for storing hydrogen is provided, the porous magnesium structure including a magnesium skeleton and pores, having a three-dimensional porous structure, wherein the magnesium skeleton has an average thickness greater than 0 nm and less than or equal to 50 nm.
[0012] The magnesium skeleton may include a magnesium body and an oxide film located on a surface of the magnesium body.
[0013] The oxide film may include magnesium oxide, wherein the magnesium oxide may include MgO.
[0014] The magnesium body and the oxide film may have a molar ratio of 1:1 to 1:5.
[0015] The average diameter of the pores may be from 35 nm to 65 nm.
[0016] The specific surface area of porous magnesium structures can be 20m 2 / g to 40m 2 / g.
[0017] The porous magnesium structure may have a diffraction peak at 2θ of 35° to 40° in an XRD spectrum.
[0018] A transition metal may be further included on the surface of the magnesium framework, wherein the transition metal may include a metal having a higher standard reduction potential than magnesium.
[0019] Another example provides a method for preparing a porous magnesium structure for storing hydrogen, comprising the steps of: preparing a porous magnesium structure including a magnesium skeleton and pores by dealloying a magnesium-alkali metal alloy by placing it in a solution, wherein the solution includes an aromatic compound dissolved in an organic solvent.
[0020] The aromatic compound may include naphthalene, biphenyl, phenanthrene, anthracene, or a combination thereof.
[0021] The dealloying may be dissolving the alkali metal from the magnesium-alkali metal alloy.
[0022] The dissolved alkali metal may react with the aromatic compounds in solution to form by-products.
[0023] The method may further include, after the step of manufacturing the porous magnesium structure, the step of mixing the manufactured porous magnesium structure with a precursor containing a transition metal to manufacture the porous magnesium structure further including a transition metal.
[0024] The transition metal-containing precursor may include a chloride of a transition metal, a complex of a transition metal, or a combination thereof.
[0025] The transition metal-containing precursor may be mixed in an amount of 1 to 10 parts by weight per 100 parts by weight of the porous magnesium structure prepared above.
[0026] The porous magnesium structure further including a transition metal may have the transition metal located on a surface of the magnesium skeleton.
[0027] According to another example, a method for storing hydrogen is provided, comprising the steps of: absorbing hydrogen into a porous magnesium structure for storing hydrogen to obtain magnesium hydride; and reversibly desorbing hydrogen from the magnesium hydride.
[0028] The absorption may be carried out at a temperature of 150°C to 200°C.
[0029] The desorption may be carried out at a temperature of 250°C to 300°C.
[0030] Beneficial Effects
[0031] The porous magnesium structure for storing hydrogen according to an example may be used as a hydrogen storage material because it can absorb and desorb hydrogen at a low temperature and at a high rate.
[0032] Moreover, porous magnesium structures for hydrogen storage are environmentally friendly and can be prepared in a simple manner, thus helping to accelerate the advent of the hydrogen economy. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 is a schematic diagram of a porous magnesium structure for storing hydrogen according to an example.
[0034] Figure 2 is a schematic diagram illustrating a method of preparing a porous magnesium structure for storing hydrogen according to an example.
[0035] Figure 3 is a SEM image of the porous magnesium structure for storing hydrogen according to Example 1.
[0036] Figure 4A is a SEM image of a porous magnesium structure for storing hydrogen according to Example 1, and Figure 4B is a SEM image of the porous magnesium structure for storing hydrogen according to Comparative Example 1.
[0037] Figure 5 3 is an XRD analysis diagram of the porous magnesium structure for storing hydrogen according to Example 1 and Comparative Example 1.
[0038] Fig. 6A is the N of the porous magnesium structure for storing hydrogen according to Example 1 2 Adsorption curve, Figure 6B is a pore size distribution curve of a porous magnesium structure for storing hydrogen according to Example 1, and Figure 6C is a BET analysis graph of the porous magnesium structure for storing hydrogen according to Example 1.
[0039] Fig. 7A is an XPS analysis diagram of the porous magnesium structure for storing hydrogen according to Example 1, and Figure 7B is an XPS analysis chart of the porous magnesium structure for storing hydrogen according to Comparative Example 1.
[0040] Fig. 8A are hydrogen absorption curves of the porous magnesium structures for storing hydrogen according to Example 1 and Comparative Example 1, and Figure 8B are hydrogen desorption curves of the porous magnesium structures for storing hydrogen according to Example 1 and Comparative Example 1.
[0041] Best Mode
[0042] Unless defined otherwise, all technical and scientific terms used herein have the same meanings as commonly understood by one of ordinary skill in the art. Generally speaking, the nomenclature and laboratory procedures used herein are well known and commonly used in the art.
[0043] Hereinafter, with reference to the attached drawings, various examples of the present invention will be described in detail to facilitate the practice of those skilled in the art. The present invention can be implemented in various different forms and is not limited to the examples described herein.
[0044] In order to clearly illustrate the present invention, matters irrelevant to the description are omitted, and the same or similar components are denoted by the same reference numerals throughout the specification.
[0045] In addition, for the convenience of illustration, the size and thickness of each configuration shown in the drawings are arbitrarily indicated, and the present invention is not necessarily limited to what is shown. In the drawings, in order to clearly show each layer and region, the thickness is magnified, and in the drawings, for the convenience of illustration, the thickness of some layers and regions is exaggerated.
[0046] Furthermore, when a layer, film, region, plate, etc. is "on" or "over" another part, this includes not only when it is "directly on" another part, but also when there are other parts between them. On the contrary, when a part is "directly on" another part, it means that there are no other parts between them. Also, "on" or "over" a reference system means above or below the reference system, and does not necessarily mean "on" or "over" the reference system in a direction opposite to gravity.
[0047] In addition, unless specifically stated otherwise, throughout the specification, when a part “includes” components, it means that it may further include other components, not excluding other components.
[0048] Reference Figure 1 A porous magnesium structure for storing hydrogen according to one example is described.
[0049] Figure 1 is a schematic diagram of a porous magnesium structure for storing hydrogen according to an example.
[0050] Reference Figure 1 , a porous magnesium structure 10 for storing hydrogen according to an example has a three-dimensional porous structure including a magnesium skeleton 11 and pores 12. The magnesium skeleton 11 has an average thickness (t) greater than 0 nm and less than or equal to 50 nm.
[0051] In the porous magnesium structure 10 for storing hydrogen according to one example, hydrogen gas quickly diffuses into the interior through the pores 12, dissociates from the surface of the magnesium skeleton 11, and diffuses into the interior of the magnesium lattice in the form of hydrogen atoms. Therefore, since the diffusion distance of the nanostructured magnesium skeleton 11 is short, that is, its crystals are nanostructured, the absorption or desorption of hydrogen can occur quickly at low temperatures. Moreover, since the porous magnesium structure 10 is manufactured by nanostructuring magnesium itself without using other composite materials, it has high energy density as described later in the manufacturing method.
[0052] The average thickness (t) of the magnesium skeleton 11 may be greater than 0 nm and less than or equal to 50 nm or less, such as 1 nm to 50 nm, 1 nm to 45 nm, 1 nm to 40 nm, 5 nm to 35 nm, or 5 nm to 30 nm. When the magnesium skeleton 11 has an average thickness (t) within the above range, during the absorption and desorption of hydrogen, the diffusion distance of hydrogen atoms in the lattice is reduced, and hydrogen gas also diffuses smoothly through the pores, so that the absorption and desorption of hydrogen can be performed at a high speed.
[0053] The magnesium skeleton 11 may include a magnesium body and an oxide film on a surface of the magnesium body.
[0054] The oxide film may include magnesium oxide. Magnesium oxide may include MgO, Mg(OH) 2 or a combination thereof.
[0055] The magnesium body and the oxide film may have a molar ratio of 1:1 to 1:5, such as a molar ratio of 1:1 to 1:4. The molar ratio may be measured in a region near the surface of the magnesium skeleton, more particularly in a region having a depth of 1 nm to 10 nm from the surface of the magnesium skeleton to the interior. When the molar ratio of the magnesium body and the oxide film is within the above range, a magnesium skeleton with a good nanostructure of a thin oxide film may be obtained, the metal surface of which is very conducive to storing hydrogen. As a result, a porous magnesium structure may be obtained in which the absorption and desorption of hydrogen proceed rapidly below low temperatures.
[0056] The average diameter of the pores 12 may be 35 nm to 65 nm, such as 40 nm to 60 nm. When the average diameter of the pores is within the above range, the absorption and desorption of hydrogen may be performed at a high rate at low temperatures due to the short diffusion distance of the nanostructured magnesium skeleton 11. Here, the average diameter of the pores refers to the diameter of the major axis of the pores.
[0057] The specific surface area of the porous magnesium structure 10 can be 20 m 2 / g to 40m 2 / g, such as 20m 2 / g to 30m 2When the specific surface area of the porous magnesium structure 10 is within the above range, more magnesium can be exposed to the hydrogen gas phase, allowing absorption and desorption of hydrogen at a high rate and at a low temperature, which can be useful as a hydrogen storage material.
[0058] In an X-ray diffraction (XRD) spectrum, the porous magnesium structure 10 may have a diffraction peak at 2θ of 35° to 40°, such as 2θ of 36° to 39°. This feature of the XRD spectrum indicates that the porous magnesium structure 10 is made of pure magnesium with an extremely low impurity content. If the porous magnesium structure 10 has the above XRD spectrum, it can absorb and desorb hydrogen at a low temperature and at a fast rate, and it can be very useful as a hydrogen storage material.
[0059] The porous magnesium structure 10 may further include a transition metal on the surface of the magnesium skeleton 11 .
[0060] Since transition metals can act as catalysts in the absorption and desorption reactions of hydrogen, their introduction into the porous magnesium structure 10 allows for the absorption and desorption of hydrogen at a faster rate. In addition, since the porous magnesium structure according to one example is manufactured in a non-corrosive reaction environment, as described later, this environment is conducive to the introduction of the transition metal acting as a catalyst into the porous magnesium structure 10 because it has a metal magnesium surface that is conducive to the introduction of the transition metal.
[0061] The transition metal can be any metal having a higher standard reduction potential than magnesium. Examples include, but are not limited to, Ni, Ti, Co, or any combination thereof.
[0062] Hereinafter, a method of manufacturing the above-mentioned porous magnesium structure 10 will be described.
[0063] The porous magnesium structure 10 according to one example is manufactured in a non-corrosive solution phase, in particular, by placing a magnesium-alkali metal alloy in a solution to dealloy it. In this case, the solution is an aromatic compound dissolved in an organic solvent.
[0064] Dealloying means that alkali metal is selectively dissolved from the magnesium-alkali metal alloy, and the remaining magnesium atoms grow into a porous magnesium structure 10 consisting of a magnesium skeleton 11 having a nanoscale size, ie, a nanometer thickness, and pores 12 having a nanometer diameter through a self-assembly process.
[0065] Conventional methods for forming porous metals are mainly based on the use of corrosive strong acids to dealloy them from alloys, and are mainly used for precious metals or transition metals. The use of corrosive materials is not only environmentally unfriendly, but also unsuitable for elements with a high tendency to oxidize, such as magnesium. Magnesium is an easily oxidizable element, and oxidation or deactivation of the magnesium surface adversely affects the hydrogen storage properties of magnesium, so it is very important to minimize it to manufacture porous magnesium structures. If the porous magnesium structure is dealloyed by using corrosive strong acids or by dissolving lithium from an oxidized electrode, the surface of the magnesium will be largely oxidized due to the sensitivity of magnesium to oxidation, thereby reducing the hydrogen storage properties.
[0066] In one example, a porous metal structure has been successfully synthesized from magnesium by synthesizing in a non-corrosive solution phase, unlike conventional porous metal synthesis methods. According to one example, the porous magnesium structure 10 is prepared by dealloying in a reduction reaction environment in a non-corrosive solution. Its manufacture does not require corrosive materials or electrochemical equipment that are typically used to produce dealloying, and can therefore be manufactured in an environmentally friendly and simple process, which can help accelerate the advent of the hydrogen economy.
[0067] In addition, the transition metal that catalyzes the absorption and desorption reaction of hydrogen cannot be introduced into a corrosive environment, and according to one example, in a reduction reaction environment in a non-corrosive solution, the transition metal will not be leached, so the transition metal can be introduced into the porous magnesium structure 10 in the same process without additional treatment. Therefore, the porous magnesium structure 10 into which the transition metal is introduced can further accelerate the absorption and desorption of hydrogen.
[0068] In the case of using a magnesium-alkali metal alloy as a raw material, the alkali metal may be, for example, but not limited to, Li, Na, K, and the like.
[0069] In the solution in which the aromatic compound is dissolved in the organic solvent, the aromatic compound may be, for example, a compound having two or more aromatic rings. Specifically, the aromatic compound may include, for example, but not limited to, naphthalene, biphenyl, phenanthrene, anthracene, or a combination thereof.
[0070] In the solution in which the aromatic compound is dissolved in the organic solvent, the organic solvent may be any solvent capable of dissolving the aromatic compound without limitation. Examples of the organic solvent include tetrahydrofuran (THF), diethyl ether, hexamethylphosphoramide (HMPA), and 1,2-dimethoxyethane.
[0071] The alkali metal dissolved by dealloying can react with the aromatic compound in the solution to form a byproduct. The formed byproduct can be used as a reducing agent to protect the porous magnesium structure 10 from oxidation. In addition, the byproduct can be further used as a reducing agent in processes such as the synthesis of nanoparticles.
[0072] As an example, refer to Figure 2 A method of manufacturing the porous magnesium structure 10 according to an example is described. Figure 2 It is illustrated for explanation purposes, but the method of manufacturing a porous magnesium structure according to one example is not limited thereto.
[0073] Figure 2 is a schematic diagram illustrating a method of preparing a porous magnesium structure for storing hydrogen according to an example.
[0074] Reference Figure 2 According to one example, the porous magnesium structure 10 can be prepared by placing a magnesium-lithium alloy processed in the form of a 1 mm to 5 mm block in a solution of naphthalene dissolved in a THF solvent to dealloy it. In particular, only the lithium in the magnesium-lithium alloy crystal is selectively dissolved, and the remaining magnesium atoms grow into a nanoscale porous magnesium structure 10 through a self-assembly process. At this time, the dissolved lithium can react with naphthalene to form naphthalene lithium. The formed naphthalene lithium can act as a reducing agent to protect the porous magnesium structure 10 from oxidation.
[0075] According to another example, after preparing the porous magnesium structure by dealloying as described above, a step of mixing the prepared porous magnesium structure 10 with a precursor containing a transition metal may be further performed. By further performing the above steps, a porous magnesium structure further including a transition metal may be prepared.
[0076] The transition metal-containing precursor may include a chloride of a transition metal, a complex of a transition metal, or a combination thereof. The transition metal may include Ni, Ti, Co, or a combination thereof.
[0077] The complex of the transition metal may be a compound in which a ligand such as cyclopentadiene is firmly bonded to the central metal.
[0078] The transition metal-containing precursor may be mixed in an amount of 1 to 10 parts by weight, such as 2 to 9 parts by weight, per 100 parts by weight of the porous magnesium structure prepared by dealloying in the previous step. When the transition metal-containing precursor is mixed within the above range, the transition metal may be stably introduced into the porous magnesium structure without leaching, thereby obtaining a porous magnesium structure capable of absorbing and desorbing hydrogen at a faster rate.
[0079] The porous magnesium structure further including a transition metal prepared by the above method may specifically include a magnesium skeleton 11 and pores 12 , wherein the transition metal is located on the surface of the magnesium skeleton 11 .
[0080] The porous magnesium structure according to one example is produced in a solution-phase reaction at room temperature and is therefore easy to mass-produce. In addition, according to one example, the magnesium-alkali metal alloy can be easily dealloyed by placing it in a solution and stirring it, making the manufacturing method easy and simple.
[0081] A method of storing hydrogen using the above-described porous magnesium structure 10 is described below.
[0082] A hydrogen storage method according to one example is achieved by absorbing hydrogen in the aforementioned porous magnesium structure 10 and reversibly desorbing it. Specifically, it can be performed by applying hydrogen gas to the porous magnesium structure 10 at a predetermined temperature to absorb hydrogen to obtain magnesium hydride, and then increasing the temperature and removing the hydrogen gas to reversibly desorb hydrogen from the magnesium hydride.
[0083] The absorption of hydrogen can be performed at a temperature of 150° C. to 200° C., such as at a temperature of 160° C. to 190° C. The desorption of hydrogen can be performed at a temperature of 250° C. to 300° C., such as at a temperature of 260° C. to 290° C. Since rapid absorption and desorption of hydrogen can occur even at low temperatures, such as within the above temperature range, the porous magnesium structure according to one example can be effectively used as a hydrogen storage material.
[0084] The porous magnesium structure according to one example can absorb and desorb about 5% of hydrogen within 40 minutes relative to the total weight of the porous magnesium structure.
[0085] The following examples describe the above examples in more detail. However, the following examples are for illustrative purposes only and are not intended to limit the scope of the claims.
[0086] Fabricating porous magnesium structures
[0087] Example 1
[0088] By making Mg-Li alloy (Mg 15 Li 85 The porous magnesium structure was prepared by dealloying the above alloy (NEBA Co.) by adding 100 mg of the above alloy to 110 mL of a solution in which 0.16 M naphthalene was dissolved in tetrahydrofuran (THF) solvent and stirring.
[0089] Comparative Example 1
[0090] The porous magnesium structure was prepared by electrochemical dealloying by placing a Mg-Li alloy foil as a positive electrode and a Li foil as a negative electrode and applying a voltage of 1.5 V thereto.
[0091] In particular, upon application of voltage, Li is selectively removed from the Mg-Li alloy at the positive electrode to produce a porous magnesium structure, and at the negative electrode, the removed Li grows into dendrites.
[0092] Evaluation 1: SEM analysis
[0093] Scanning electron microscope (SEM) analysis was performed to confirm the structure of the porous magnesium structure according to Example 1 and Comparative Example 1, and the results are as follows: Figures 3 to 4B shown.
[0094] Figure 3 is a scanning electron microscope (SEM) image of the porous magnesium structure for storing hydrogen according to Example 1.
[0095] Reference Figure 3 It can be seen that the porous magnesium structure according to an example includes a magnesium skeleton and pores and has a three-dimensional porous structure, wherein the average thickness of the magnesium skeleton is 50 nm or less.
[0096] Figure 4A is a SEM image of a porous magnesium structure for storing hydrogen according to Example 1, and Figure 4B is a SEM image of the porous magnesium structure for storing hydrogen according to Comparative Example 1.
[0097] Reference Figure 4A and Figure 4B It can be seen that the porous magnesium structure according to Example 1 has a magnesium skeleton and pores that are both nanoscale, while in the case of Comparative Example 1, the pores are very large, the size is outside the nanoscale, and the variation of the pore diameter is also very large.
[0098] Evaluation 2: XRD analysis
[0099] X-ray diffraction (XRD) analysis was performed to confirm the crystal structure of the porous magnesium structure according to Example 1 and Comparative Example 1, and the results are as follows: Figure 5 shown.
[0100] Figure 5 3 is an XRD analysis diagram of the porous magnesium structure for storing hydrogen according to Example 1 and Comparative Example 1.
[0101] Reference Figure 5 It can be seen that in the XRD spectrum, the porous magnesium structure according to one example has a diffraction peak at 2θ between 35° and 40°, indicating that the crystal structure of Mg is well formed.
[0102] Evaluation 3: Specific surface area analysis
[0103] The specific surface area of the porous magnesium structure according to Example 1 was measured by the Brunauer-Emmett-Teller (BET) method, and the results are as follows: FIG. 6A to FIG. 6C shown.
[0104] Fig. 6A is the N of the porous magnesium structure for storing hydrogen according to Example 1 2 Adsorption curve, Figure 6B is a pore size distribution curve of a porous magnesium structure for storing hydrogen according to Example 1, and Figure 6C is a BET analysis graph of the porous magnesium structure for storing hydrogen according to Example 1.
[0105] Reference FIG. 6A to FIG. 6C It can be seen that the porous magnesium structure according to one example has a 2 / g to 40m 2 The specific surface area in the range of 1000 Å / g allows the absorption and desorption of hydrogen at a fast rate and at low temperature.
[0106] Evaluation 4: XPS analysis
[0107] In order to confirm the oxide film structure in the porous magnesium structure according to Example 1 and Comparative Example 1, X-ray photoelectron spectroscopy (XPS) analysis (Mg 2p XPS) was performed, and the results are as follows: Fig. 7A and Figure 7B shown.
[0108] Fig. 7A is an XPS analysis diagram of the porous magnesium structure for storing hydrogen according to Example 1, and Figure 7B is an XPS analysis chart of the porous magnesium structure for storing hydrogen according to Comparative Example 1.
[0109] Reference Fig. 7A and Figure 7B , it can be seen that the porous magnesium structure according to one example includes both the magnesium body and the oxide film located on the surface thereof. It can also be seen that in Example 1, in a region with a depth of 1 nm to 10 nm from the surface of the magnesium skeleton to the inside, the molar ratio of the magnesium body to the oxide film is about 1:2, and according to one example, it is in the molar ratio range of 1:1 to 1:5. On the other hand, in Comparative Example 1, the molar ratio of the magnesium body to the oxide film is about 1:6.
[0110] From this, it can be seen that the porous magnesium structure according to one example has a relatively thin oxide film, and it can be expected that absorption and desorption of hydrogen can occur at a rapid rate at a low temperature.
[0111] Evaluation 5: Hydrogen absorption and desorption rates
[0112] The absorption and desorption rates of hydrogen of the porous magnesium structure according to Example 1 and Comparative Example 1 were measured, and the results are as follows: Fig. 8A and Figure 8B shown.
[0113] The measurements were performed using a Sievert apparatus, which is a pressure / volume based measurement, in a hydrogen pressurized environment at 200°C and 16 bar for the absorption of hydrogen and in a static vacuum environment at 300°C and 0 bar for the desorption of hydrogen.
[0114] Fig. 8A are hydrogen absorption curves of the porous magnesium structures for storing hydrogen according to Example 1 and Comparative Example 1, and Figure 8B are hydrogen desorption curves of the porous magnesium structures for storing hydrogen according to Example 1 and Comparative Example 1.
[0115] Reference Fig. 8A and Figure 8B , it can be seen that the porous magnesium structure according to Example 1 allows absorption and desorption of hydrogen at a faster rate than that of Comparative Example 1.
[0116] Although preferred embodiments of the present invention have been described in detail above, the scope of the present invention is not limited thereto, and various modifications and improvements made by those skilled in the art using the basic concepts of the present invention as defined in the following claims are also within the protection scope of the present invention.
Claims
1. A porous magnesium structure for storing hydrogen, comprising a magnesium skeleton and pores, and having a three-dimensional porous structure, The magnesium skeleton has an average thickness greater than 0 nm and less than or equal to 200 nm.
2. The porous magnesium structure for storing hydrogen according to claim 1, wherein: The magnesium skeleton includes a magnesium body and an oxide film on a surface of the magnesium body.
3. The porous magnesium structure for storing hydrogen according to claim 2, wherein: The oxide film includes magnesium oxide, and the magnesium oxide includes MgO.
4. The porous magnesium structure for storing hydrogen according to claim 2, wherein: The magnesium body and the oxide film have a molar ratio of 1:1 to 1:
5.
5. The porous magnesium structure for storing hydrogen according to claim 1, wherein: The pores have an average diameter of 20 nm to 200 nm.
6. The porous magnesium structure for storing hydrogen according to claim 1, wherein: The porous magnesium structure has a 30m 2 / g to 40m 2 / g specific surface area.
7. The porous magnesium structure for storing hydrogen according to claim 1, wherein: The porous magnesium structure has a diffraction peak at 2θ of 35° to 40° in an XRD spectrum.
8. The porous magnesium structure for storing hydrogen according to claim 1, further comprising a transition metal located on a surface of the magnesium skeleton.
9. The porous magnesium structure for storing hydrogen according to claim 8, wherein: The transition metal includes a metal having a higher standard reduction potential than magnesium.
10. A method for preparing a porous magnesium structure for storing hydrogen, comprising preparing a porous magnesium structure having a magnesium skeleton and pores by dealloying a magnesium-alkali metal alloy in a solution in which an aromatic compound is dissolved in an organic solvent.
11. The method for preparing a porous magnesium structure for storing hydrogen according to claim 10, wherein: The aromatic compound includes naphthalene, biphenyl, phenanthrene, anthracene or a combination thereof.
12. The method for preparing a porous magnesium structure for storing hydrogen according to claim 10, wherein: The dealloying is performed by dissolving the alkali metal from the magnesium-alkali metal alloy.
13. The method for preparing a porous magnesium structure for storing hydrogen according to claim 12, wherein: The dissolved alkali metal reacts with the aromatic compounds in the solution to form by-products. 14 . The method for preparing a porous magnesium structure for storing hydrogen according to claim 10 , further comprising, after preparing the porous magnesium structure, mixing the prepared porous magnesium structure with a transition metal-containing precursor to produce a transition metal-containing porous magnesium structure.
15. The method for preparing a porous magnesium structure for storing hydrogen according to claim 14, wherein: The transition metal-containing precursor includes a transition metal chloride, a transition metal complex, or a combination thereof.
16. The method for preparing a porous magnesium structure for storing hydrogen according to claim 14, wherein: The transition metal-containing precursor is mixed in an amount of 1 to 10 parts by weight per 100 parts by weight of the prepared porous magnesium structure.
17. The method for preparing a porous magnesium structure for storing hydrogen according to claim 14, wherein: The transition metal-containing porous magnesium structure is located on the surface of the magnesium skeleton.
18. A method for storing hydrogen, comprising: Absorbing hydrogen into the hydrogen storage porous magnesium structure according to any one of claims 1 to 9 to obtain magnesium hydride; as well as Hydrogen is reversibly desorbed from the magnesium hydride.
19. The method for storing hydrogen according to claim 18, wherein: The absorption is carried out at a temperature of 150°C to 200°C.
20. The method for storing hydrogen according to claim 18, wherein: The desorption is performed at a temperature of 250°C to 300°C.